Formative evaluation in higher education in the countries of the Andean community - Verástegui Sisniegas, Rosa Mercedes (2021)
The objective of the following theoretical reflection essay is to analyze the scientific contributions to formative assessment in higher education in the countries of the Andean Community of Nations (Bolivia, Colombia, Ecuador, and Peru) through an exploration of the last nine years. The dimensions studied correspond to teaching skills, evaluation, feedback, and educational quality, through a systematic review using the PRISMA Declaration method, where 11 scientific articles were reviewed in the online bibliographic databases of the most important.